Avaliação para as aprendizagens em matemática: dinâmicas e práticas pedagógicas de professores dos anos iniciais a partir do questionário SAEB/2015 - PEIXOTO, Wilton Medeiros (2020)
This article aims at mapping recurrent pedagogical practices and dynamics among teachers of the 5th grade teaching mathematics in public schools in Belém. The analyzes focus on the empirical evidence presented by Black and William, which point to formative evaluation as more adequate for learning. We use as a research tool the microdata of SAEB (2015). The results of the research present frequencies of six practices and seven common dynamics among teachers.